Report on Teacher Education and Training for the Primary Level - Trinidad and Tobago. Teacher Education Committee (Ministry of Education, Trinidad and Tobago, 1980)
The report forms part of the report of the committee on teacher training and teacher education for all levels and for all areas of the education system in Trinidad and Tobago. It give s brief outline of, and comments on, the existing system of teacher education and training for the primary level, and makes proposals for the improvement of future plans.
Chairman: C.V. Gocking Copies: 2
Keywords: teacher education; primary education